2018
DOI: 10.3390/w10050564
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Long-Term Hydrological Impact of Climate Change Using an Ensemble Approach and Comparison with Global Gridded Model-A Case Study on Goodwater Creek Experimental Watershed

Abstract: Potential impacts of climate change on the hydrological components of the Goodwater Creek Experimental Watershed were assessed using climate datasets from the Coupled Model Intercomparison Project Phase 5 and Soil and Water Assessment Tool (SWAT). Historical and future ensembles of downscaled precipitation and temperature, and modeled water yield, surface runoff, and evapotranspiration, were compared. Ensemble SWAT results indicate increased springtime precipitation, water yield, surface runoff and a shift in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 79 publications
(93 reference statements)
2
23
0
Order By: Relevance
“…On the other hand, Kang et al [8] and others indicated increased crop production with a modest rise in average temperature of 1-3 • C, but decreasing yields above this range. From the hydrological modeling perspective, the Soil and Water Assessment Tool (SWAT) [11] has been used to assess quality and quantity issues [12,13] to identify critical source areas [14] and impacts on crop-yield [15,16] due to changes in climate and land uses in order to suggest improved management practices [17].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Kang et al [8] and others indicated increased crop production with a modest rise in average temperature of 1-3 • C, but decreasing yields above this range. From the hydrological modeling perspective, the Soil and Water Assessment Tool (SWAT) [11] has been used to assess quality and quantity issues [12,13] to identify critical source areas [14] and impacts on crop-yield [15,16] due to changes in climate and land uses in order to suggest improved management practices [17].…”
Section: Introductionmentioning
confidence: 99%
“…Gautam et al. () also found future spring and mean annual water yield will increase in the Goodwater Creek, Missouri due to projected changes in climate conditions.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies in the Midwest region had simulated an increase in spring precipitation and a decrease in summer precipitation under RCP 4.5 and RCP 8.5 (Gautam et al. ). Neupane and Kumar () also found precipitation during the spring months will increase, but will decrease in the summer by the end of the 21st Century in the Big Sioux River watershed, which is located in the North Central region and drains into the Missouri River.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected gamma-based quantile mapping as a bias correction technique as it has been reported as less sensitive to differences in climate projection time frame and emissions scenarios, when compared to empirical quantile mapping (Lafon et al 2013). Comprehensive bias correction details for precipitation adjustments can be found in Gautam et al (2018). After adjusting projections, we selected three models based on the following criteria for years 2070-2099: (1) an average model, representing the most typical precipitation conditions projected in RCP4.5 scenarios;…”
Section: Future Climate Projections and Historical Data: Approach Utimentioning
confidence: 99%